2013
DOI: 10.7870/cjcmh-2013-007
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent can Adolescent Suicide Attempts be Attributed to Violence Exposure? A Population-Based Study from Western Canada

Abstract: Suicide is the second leading cause of death among adolescents in Canada and globally. The purpose of our study was to calculate what proportion of adolescent suicide attempts could be prevented in the absence of verbal, physical and sexual violence. Using the province-wide 2008 British Columbia Adolescent Health Survey (N=29,315) we calculated population-attributable fractions for each type of violence, as well as exposure to any violence, separately by gender, among adolescents age 12-19. We found violence v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…For example, in the BC Adolescent Health Survey, sexual violence was linked to a heightened risk of suicide attempts for both boys and girls. 30 Our results suggest few gender differences in the association between child sexual abuse and the correlates examined while controlling for other forms of maltreatment. Our findings thus concur with past studies conducted with clinical samples of minor victims of sexual abuse and failed to identify gender differences in the severity of internalized, externalized, and trauma symptoms.…”
Section: Girls Boysmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, in the BC Adolescent Health Survey, sexual violence was linked to a heightened risk of suicide attempts for both boys and girls. 30 Our results suggest few gender differences in the association between child sexual abuse and the correlates examined while controlling for other forms of maltreatment. Our findings thus concur with past studies conducted with clinical samples of minor victims of sexual abuse and failed to identify gender differences in the severity of internalized, externalized, and trauma symptoms.…”
Section: Girls Boysmentioning
confidence: 57%
“…For example, in the BC Adolescent Health Survey, sexual violence was linked to a heightened risk of suicide attempts for both boys and girls. 30…”
Section: Discussionmentioning
confidence: 99%
“…12 Verbal sexual abuse How many times have you had unwanted sexual comments or jokes directed at you? 22 Did anyone hurt your feelings by saying or writing something sexual about your body? 12 Online victimization Did anyone on the Internet ever ask you sexual questions about (himself/herself/yourself) or try to get you to talk online about sex when you did not want to talk about those things?…”
Section: Resultsmentioning
confidence: 99%
“…59 A population study ( n = 29,315; 48% males) reported that adolescent males were more likely than females to report physical violence (46% vs. 30%), and such experiences increased their odds 5-fold for making a suicide attempt; boys who experienced sexual violence were 3 times more likely than girls to make a suicide attempt. 70 Boys who reported being bullied were 2 to 3.5 times more likely to report suicidal ideation, mental distress, and delinquency. 60 Deviant behaviors were also a significant predictor of boys making a suicide attempt, 64 and among high school students ( n = 712; 360 males), boys with suicidal ideation scored higher on negative attribution style, hopelessness, and depression.…”
Section: Resultsmentioning
confidence: 95%